Management of Oral and Dental Health in Paediatric Practice: A Comprehensive Review from Diagnosis to Referral - Emre Çelik (Journal of Bursa Faculty of Medicine, 2026)
Oral and dental health is an intrinsic component of children’s overall health and well-being. Dental caries remains the most common chronic disease affecting children globally and, despite being preventable, continues to significantly impact pediatric health and psychosocial development.This review aims to define the fundamental preventive approaches pediatricians are expected to follow in light of global guidelines, the critical links between oral health and systemic diseases, and the clinical practice gaps in Türkiye and internationally.Pediatricians serve as a strategic “first point of contact” as they are visited more frequently than dentists, particularly during the first three years of life. Global authorities, such as the AAP and USPSTF, recommend performing oral health risk assessments starting at six months of age, initiating the first dental visit by age one or upon the eruption of the first tooth, and utilizing evidence-based interventions, such as Fluoride Varnish (FV). Contemporary dietary habits—frequent free-sugar intake, ultra-processed foods and acidic or sugar-sweetened beverages—are now the leading modifiable drivers of caries and erosive tooth wear, and brief dietary counselling is an integral part of pediatric preventive care. While the review details the reciprocal relationship between oral pathologies and systemic conditions—such as Chronic Kidney Disease, Type 1 Diabetes, and congenital heart disease—it highlights a significant “clinical practice gap” resulting from insufficient training and knowledge despite physicians’ generally positive attitudes.It is essential to adopt oral health as an absolute “pediatric necessity”, incorporate interprofessional rotations into medical curricula, integrate dietary counselling and public awareness programmes starting in early childhood, and develop a single, standardized interdisciplinary guideline for all healthcare professionals to enhance the overall quality of life for children.